Analysis of Higher-Order-Thinking Skill (HOTS) Questions in the Class V Elementary Student's Books Theme 3 - Sarah Fazilla; Fauziana; Parida Hanum Siregar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The lack of higher-order thinking skills (HOTS) questions in student books causes students to be inadequate to solve HOTS questions. Hence, it resulted in the unachieved program of expected Curriculum 13 learning program, namely higher-order-thinking skills (HOTS) and 21st-century skills. This study aims to determine whether the questions in the Class V Student Book Theme 3, "Healthy Food," published by the Ministry of Education and Culture in 2017, qualify as HOTS questions. Additionally, it seeks to assess the quality of these HOTS questions in the Student Book for Class V Theme 3, "Healthy Food," published by the Ministry of Education and Culture in 2017. The research uses the content analysis method. The data analysis was conducted qualitatively by analyzing document data—specifically on the questions in the Class V Student Book Theme 3 of "Healthy Food", elaborating its questions, and being separated based on the Bloom's Taxonomy category levels, ranging from C1 to C6. The analysis results are presented as percentages for each question type. The research subject was four sub-themes of the class V Student Book theme 3, "Healthy Food," published by the Ministry of Education and Culture in 2017. Documentation was the chosen technique and tool for data collection in this study. The research findings reveal that at the analyzing level (C4), the items constituted 35.2%, at the evaluating level (C5), the items comprised 23.5%, and at the creating level (C6), the items constituted 76.4%. As a result, the quality of the questions in the class V Student Book theme 3, "Healthy Food," indicates that a significant majority of 76.4% of questions, which means that ̳most of them‘ are centered around the creation level.